Pelatihan Pembuatan Alat Musik Edukatif dari Limbah Sebagai Integrasi Seni dan Pendidikan Lingkungan - Retnoning A.W. Astuti; Marwati Marwati; Putri P. Utami; Mariam N.P. Achadiath; Dominggas Sobi; Reza N. Gondokusumo (JURNAL PENGABDIAN PAPUA, 2026)
This community service study aims to enhance creativity, practical skills, and environmental awareness of prospective elementary school teachers through training in the production of educational musical instruments from inorganic waste using a STEAM approach. The program was conducted at the Primary Teacher Education Study Program, Cenderawasih University, using a qualitative descriptive method. Participants followed stages including socialization, material delivery, instrument construction practice, sound testing, presentation, and reflection. Waste materials such as plastic bottles, cardboard, cans, and used rubber were transformed into maracas, drums, and other simple musical instruments. The results show increased creativity indicated by diverse instrument designs, improved sound exploration skills, and better material selection abilities. Participants also demonstrated improved understanding of sound concepts, recycling, and sustainable education principles. The activity strengthened critical thinking and collaboration skills. Findings indicate that integrating environmental education, arts, and STEAM effectively develops innovative and environmentally conscious teacher candidates. Therefore, waste-based learning can serve as a contextual instructional strategy relevant to twenty-first century education. It also contributes to strengthening pedagogical competence and sustainability-oriented teaching practices in elementary education in Indonesia in response to global environmental challenges while supporting innovation in learning design and student engagement through hands-on contextual learning experiences in sustainable education practice.